Explaining Differences in Remuneration Rates of Nursing Homes in Germany - Roman Mennicken; Boris Augurzky; Heinz Rothgang; Jürgen Wasem (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2010)
Remuneration rates of German nursing homes are prospectively negotiated between long-term care insurance (LTCI) and social assistance on the one side and nursing homes on the other. They differ considerably across regions while there is no evidence for substantial differences in care provision. This paper explains the differences in the remuneration rates by observable characteristics of the nursing home, its residents and its region with a special focus on the largest federal state North-Rhine-Westphalia, in which the most expensive nursing homes are located. We use data from the German Federal Statistical Office for 2005 on all nursing homes that off er full-time residential care for the elderly. We find that differences in remuneration rates can partly be explained by exogenous factors. Controls for residents, nursing homes, and district characteristics explain roughly 30% of the price difference; 40% can be ascribed to a regionally different kind of negotiation between nursing homes and LTCI. 30% of the raw price difference remains unexplained by observable characteristics. – – Die Vergütung in Pflegeheimen wird zwischen der Pflegeversicherung, Sozialhilfeträgern und dem jeweiligen Pflegeheim verhandelt. In der Höhe der Vergütung zeigen sich maßgebliche regionale Unterschiede. Die vorliegende Arbeit hat zum Ziel, Gründe für die höheren Heimentgelte in Nordrhein-Westfalen zu ermitteln. Eine Auswertung von Daten der Statistischen Ämter der Länder und des Bundes über Pflegeeinrichtungen mit einer Spezialisierung auf Altenpflege zeigt, dass die Unterschiede teilweise erklärbar sind: Mit Merkmalen der Heime, der Bewohner und der Region lassen sich ca. 30% des Preisunterschieds erklären. Weitere 40% sind wahrscheinlich auf regionale Unterschiede in den Verhandlungen zurückzuführen, während die letzten 30% nicht anhand von beobachtbaren Merkmalen erklärt werden können.
Keywords: I11; I18; 330; nursing homes; determinants of remuneration rates; regional price differences